Sistem Pakar Diagnosa Penyakit Avian Influenza Pada Bebek Menggunakan Metode Certainty Factor - Arief Gilang Ramadhan; Teguh Susyanto; Iwan Ady Prabowo (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2019)
Ducks are widely farmed poultry animals, because of its large population, the disease is also caused a lot. In avian influenza disease is an infectious animal disease caused by a virus and can infect humans. Avian invluenza is also a cause of decreased quality of meat and eggs, can even cause death in ducks. Disease in ducks is difficult to know because people have no prior experience. Communities and breeders find it difficult to take appropriate action on ducks affected by avian influenza so that they can be fatal. During 2012 - 2017 there were 1856 cases of bird flu in Indonesia. In October 2017 there were 3 cases of avian invluenza. Where 900 ducks died. From the explanation above, an expert system is needed to diagnose avian influenza. This system can help ordinary people and farmers who do not have experience in dealing with avian influenza. Disease data and symptoms of avian influenza that will be entered into this expert system can be obtained from interviews with experts and see references of knowledge about duck symptoms. So that this expert system can help in dealing with AI disease. In testing the validity, the calculation of the system manually and from expert diagnosis are the same. So that this application is feasible to use for the community and breeders.